Legal Protection for Victims of Artificial Intelligence-based Pornography in the Form of Deepfakes According to Indonesian Law - Monique, Cindy; ., Tongat; Wulandari, Siti; Bhirini Slamet, Aprilia (KnE Social Sciences, 2024)
Deepfake is an artificial intelligence-based technique for synthesizing an image of a person, using a special method to combine images or videos to make the result look realistic (POLRI 2020). Deepfake is a relatively new type of technology that allows you to download deepfake apps for free. Anyone can access the Deepfake app to create freely edited videos and images. The original purpose of using deepfakes was entertainment on TV and social media. But over time, technology is used as a tool to mislead people and spread misinformation. Deepfakes can undermine public trust, especially when it comes to big and famous people. Not only fake videos but reputation is also easily damaged by this technique. Keywords: deepfake, artificial intelligence, information and transaction electronic